2011
DOI: 10.1371/journal.pone.0023637
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Extracellular Trap (NET)-Mediated Killing of Pseudomonas aeruginosa: Evidence of Acquired Resistance within the CF Airway, Independent of CFTR

Abstract: The inability of neutrophils to eradicate Pseudomonas aeruginosa within the cystic fibrosis (CF) airway eventually results in chronic infection by the bacteria in nearly 80 percent of patients. Phagocytic killing of P. aeruginosa by CF neutrophils is impaired due to decreased cystic fibrosis transmembrane conductance regulator (CFTR) function and virulence factors acquired by the bacteria. Recently, neutrophil extracellular traps (NETs), extracellular structures composed of neutrophil chromatin complexed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
175
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(182 citation statements)
references
References 82 publications
7
175
0
Order By: Relevance
“…Whether NETs trap and kill P. aeruginosa is controversial. We, along with others, reported that the nonmucoid cystic fibrosis-derived P. aeruginosa strains were sensitive to NET trapping while the mucoid strains were resistant (13)(14)(15). In contrast, Parker et al reported that P. aeruginosa was not sensitive to NET-mediated killing (16).…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…Whether NETs trap and kill P. aeruginosa is controversial. We, along with others, reported that the nonmucoid cystic fibrosis-derived P. aeruginosa strains were sensitive to NET trapping while the mucoid strains were resistant (13)(14)(15). In contrast, Parker et al reported that P. aeruginosa was not sensitive to NET-mediated killing (16).…”
mentioning
confidence: 60%
“…Based on the proteomic profile of NETs, the expectation was that NETs carry antimicrobial activity. The bactericidal properties of NETs have attracted scientific interest; however, the question of whether NETs are capable of trapping or killing P. aeruginosa remains contentious (14,16,28). To determine the functional significance of NETs, in vitro experiments addressing NET-mediated capture of P. aeruginosa and killing were carried out.…”
Section: Resultsmentioning
confidence: 99%
“…82 Whereas NETs are sufficient to kill Pseudomonas grown in suspension, during diseases such as cystic fibrosis, the bacteria changes to a mucoid type and can become NET resistant. 83 By contrast, other groups have not been able to demonstrate significant direct killing by NETs. In the case of S aureus, despite clear trapping by the NETs, DNase treatment liberated living bacteria that were capable of proliferation.…”
Section: Direct Net Antimicrobial Activitymentioning
confidence: 96%
“…The authors in this study showed that treatment with sialidase or use of P. aeruginosa strains lacking in sialic acids led to increased NET production compared with sialic acid-positive strains. Furthermore, paired P. aeruginosa strains isolated from patients with CF at early and late stages of disease showed that resistance to NET-mediated killing evolved over time, and correlated with the development of the mucoid phenotype characterized by excess alginate production (34). However, a mutant P. aeruginosa strain that overexpressed alginate did not show increased survival on incubation with PMA-treated neutrophils, suggesting that the acquired resistance of P. aeruginosa to NETmediated killing in the CF airway was due to an as-yet unknown mechanism (34).…”
Section: Pseudomonas Aeruginosa: Net Inhibition and Resistancementioning
confidence: 99%